1953
DOI: 10.1021/ac60081a019
|View full text |Cite
|
Sign up to set email alerts
|

Small Amounts of Uranium in Presence of Iron

Abstract: The direct colorimetric determination of uranium, in the presence of moderate or large amounts of iron, is not possible by other methods. By the 8-quinolinol method, uranium may be determined in the presence of 500 mg. of iron, 50 mg. of copper, 20 mg. of nickel, or 20 mg. of cobalt without prior separations. In conjunction with the hydrolytic separation by which uranium is separated from most of the colored ions but not iron, uranium may be determined colorimetrically, as a routine technique. With an ordinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1955
1955
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…ion Fe(C9H6NO)+2 (251), and the basic salt FeCl(C9HeNO)2 is also known (101). Complex ferric compounds such as the fluoride and phosphate are said to give the same color reaction as the free ferric ion; only the ferrocyanide ion is sufficiently stable to give no color (265). A red ferrous oxinate can be prepared (131,306) but is stable only under reducing conditions (166).…”
Section: Elements Of Group VIImentioning
confidence: 99%
“…ion Fe(C9H6NO)+2 (251), and the basic salt FeCl(C9HeNO)2 is also known (101). Complex ferric compounds such as the fluoride and phosphate are said to give the same color reaction as the free ferric ion; only the ferrocyanide ion is sufficiently stable to give no color (265). A red ferrous oxinate can be prepared (131,306) but is stable only under reducing conditions (166).…”
Section: Elements Of Group VIImentioning
confidence: 99%
“…4. For the functional group quinoline-8-ol, the optimum pH range for extraction of UO 2 2+ is 4.7-8 [28]. Uranyl chemistry is complicated due to hydrolysis phenomenon.…”
Section: Optimization Studiesmentioning
confidence: 99%
“…Modified procedures with dibenzoylmethane were used by Adams and Maeck (1), Francois (3), and Pribil and Jelinek (IS). Other methods for the determination of uranium have been reported by Silverman, Moudy, and Hawley (20) and Nietzel and De Sesa (12). While systematically studying the reactivity of a large number of organic compounds with inorganic ions, it was observed that the uranyl ion gives a deep blue, stable color with the trisodium salt of 3-(2-arsonophenylazo)-4,5 -dihydroxy -2,7 -naphthalenedisulfonic acid (arsenazo).…”
Section: Literature Citedmentioning
confidence: 99%